The Outcomes of Surgical Treatment of Cubital Tunnel Syndrome. - Virbickaitė, Eglė; Dedelytė, Emilija; Knystautas, Saulius; Gindriūnas, Simas; Braziulis, Kęstutis (Lietuvos chirurgija, 2023)
Background. Cubital tunnel syndrome is the second most commonly diagnosed compressive neuropathy of the upper extremity after carpal tunnel syndrome and the most common neuropathy of the ulnar nerve. Objective. To evaluate the results of surgical treatment of patients with cubital tunnel syndrome by performing an open decompression in situ. Methods. All subjects underwent a standard operation – open surgical opening of the elbow canal (decompression in situ). On the day of surgery, after 3 months, after 6 months, pain (verbal pain scale), hand and arm function (QuickDASH), complications are evaluated. Results. There were 44 patients, 16 (36%) female, 28 (64%) male. In 50% of the patients, electroneuromyography revealed a severe degree of ulnar nerve damage, in the rest – a moderate degree of damage. Hand function for women 3 months after surgery improved by 42.046 points (according to QuickDASH), while in men it was 15.454 points (p < 0.05). Meanwhile, hand function for woman 3 months after surgery improved by 45.833 points, while in men it was 20.000 points (p < 0.05). Statistically significant differences between the groups with a moderate and severe degree of damage were found only when assessing pain according to the VAS scale at 3 months after surgery (mean VAS scores 1.2 and 2.8 respectively). A positive correlation was also observed between age and improvement in hand function between 3–6 months after surgery (p < 0.05). In older people, improvement in hand function is observed after a longer period of time after surgery, and a more pronounced improvement in hand function with a severe degree of damage (comparing function before surgery and 6 months after surgery) is experienced by younger people. Conclusions. In situ decompression of the ulnar nerve is one of the most effective methods of treating ulnar neuropathy. With this method an improvement in the function of the hand and a decrease in pain are observed.